2018
DOI: 10.1016/j.jnt.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Divisibility of the class numbers of imaginary quadratic fields

Abstract: Abstract. For a given odd integer n > 1, we provide some families of imaginary quadratic number fields of the form Q( √ x 2 − t n ) whose ideal class group has a subgroup isomorphic to Z/nZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…For example, Ram Murty [35] has shown that, if the square factor of 1 − x m is less than x m/4 /2 √ 2, then this equation has no solution. The same result is proved in [9] under the condition that x is a prime number ≥ 5. Eventually, as was pointed out by Cohn [13], it follows from the work of Nagell [30] that, for any odd number x ≥ 5, one has rk m Cl(k) ≥ 1.…”
Section: Classical Proofsupporting
confidence: 66%
“…For example, Ram Murty [35] has shown that, if the square factor of 1 − x m is less than x m/4 /2 √ 2, then this equation has no solution. The same result is proved in [9] under the condition that x is a prime number ≥ 5. Eventually, as was pointed out by Cohn [13], it follows from the work of Nagell [30] that, for any odd number x ≥ 5, one has rk m Cl(k) ≥ 1.…”
Section: Classical Proofsupporting
confidence: 66%
“…The equations of the form (1.1) are well connected with the investigation of the class number of imaginary quadratic field Q( √ −D). The authors used the solvability of some special cases of (1.1) to study the class number of certain imaginary quadratic fields in [12]- [14]. S. A. Arif and F. S. A. Muriefah [3] investigated (1.1) for the case λ = 1, n ≥ 5, m odd integers and D = p an odd prime.…”
Section: Introductionmentioning
confidence: 99%
“…Kishi [Ki10] also proved that if n ≥ 3 is odd then the class number of K 2,3,n is divisible by 3. Subsequently, there have been further generalisations of these results by Ito [Ito11] as well as Chakraborty, Hoque, Kishi and Pandey [CHKP18]. An important ingredient in these proofs is a result by Bugeuad and Shorey [BugSh01] on the number of solutions in positive integers of the generalized Ramanujan-Nagell equation.…”
Section: B Certain Infinite Families Of Quadratic Fieldsmentioning
confidence: 88%